Sonographic Determination of Gallbladder Dimension among Apparently Healthy School-aged Children in Kano Metropolis - Abubakar Aminu Abubakar; Mansur Yahuza; Ramalan Mansur; Anas Yau; Bara’atu Sani Maikusa (Acta Medica International)
Introduction: The present study was carried out to sonographically evaluate gallbladder dimensions among healthy school-aged children, thus setting up normal ranges that can be used in clinical settings. The study aimed to establish normal gallbladder dimensions in apparently healthy school-aged children within the Kano metropolis using ultrasonography. Materials and Methods: A prospective cross-sectional study of 276 healthy school-age children comprising 156 males and 120 were recruited randomly. Gallbladder length (GBL), width, height, volume, and wall thickness were recorded. The subject’s demographic information was also obtained. Data were analyzed using the SPSS version 23. Statistical significance was considered at P < 0.05. Results: Statistical analysis highlighted mean gallbladder dimensions: length (5.31 ± 0.65 cm), width (1.57 ± 0.52 cm), height (1.68 ± 0.48 cm), volume (7.31 ± 2.72 cm3), and wall thickness (2.59 ± 0.48 mm). While no significant differences were found between male and female gallbladder width and volume, notable distinctions were observed in GBL, height, and wall thickness between genders. Correlation analyses revealed significant associations between gallbladder dimensions (length, width, and volume) and demographic parameters such as age, height, weight, body mass index (BMI), body surface area, and gallbladder wall thickness (GBWT). Interestingly, gallbladder height showed no significant correlation with height, weight, or BMI, while GBWT exhibited correlations with various demographic factors. Conclusion: This research successfully established reference ranges for gallbladder dimensions in healthy school-aged children, underlining gender-specific disparities in certain measurements.